Feasibility of online group stress management training compared to web-based individual training for employees—a randomized pilot study - Leif Boß; Sandy Hannibal; Dirk Lehr (Frontiers in Psychology)
BackgroundIn recent decades, digital stress management training, typically targeted at individuals, has gained increasing attention in health promotion. While these interventions show on average moderate to high effects on stress and other mental health outcomes, their use and acceptance in practice are often low. In contrast, group training may have advantages over these shortcomings. However, despite its widespread use in traditional non-digital health promotion, there is little evidence for digital training delivered in groups.ObjectiveThis study’s aim was to explore the feasibility of live, online stress management training delivered in a group format and compare it to Internet-based training targeting individuals.MethodsEmployees (N = 62), recruited from an open access website, were randomized into either group or individual training. Group training consisted of seven weekly online appointments led by a trainer and conducted via videoconference. Individual training consisted of seven web-based sessions which included written feedback provided by an e-coach after each session. The primary outcome was perceived stress eight weeks after training initiation. Feasibility was analyzed in terms of participants’ satisfaction, adherence, and perceived benefits of both training formats, assessed via both written questionnaires and interviews.ResultsParticipants in group training [Cohen’s d = 0.9 (95% confidence interval: 0.4 to 1.5)] and individual training [1.3 (0.6 to 2.0)] both experienced statistically-significant reductions in stress, with no significant difference between the two training formats [0.25 (−0.32 to 0.83); p = 0.579]. Full adherence rates were 70% in the group training and 50% in the individual training. Participants were satisfied with both formats, appreciating the social support and personal contact of the group setting, while appreciating the time flexibility and personal contact with an e-coach offered through individual training.ConclusionThis pilot study showed promising effects for the acceptance and health-related effectiveness of stress management training delivered in a group setting via videoconference. The findings highlight the value of personal contact with a coach and peers for positive user experiences during digital stress management interventions.Clinical trial registrationhttps://drks.de/search/en/trial/DRKS00024965, DRKS00024965.